Origin of high-frequency magnetic loss of Y3Fe5O12 single crystal thin films prepared with high-throughput screening by magnetron sputtering. (January 2023) - Zhou, Tingting; Pan, Lining; Ma, Yan; Zhu, Shiqi; Tan, Guoguo; Man, Qikui
Abstract: In this study, yttrium iron garnet (Y3 Fe5 O12, YIG) single crystal nanofilms were deposited at room temperature on a Gd3 Ga5 O12 (GGG) (111) substrate via magnetron sputtering and ex situ annealing. A high-throughput method was used to systematically study the effects of sputtering gas pressure, sputtering power, and annealing temperature on the microstructure, ferromagnetic resonance signal, and high-frequency magnetic loss. The YIG films fabricated at an Argon pressure of 3 Pa, a sputtering power of 95 W, and an annealing temperature of 800 °C possessed the highest saturation magnetization and lowest linewidth (13.6 Oe). Furthermore, the maximum value of permeability (μ′) was 25.54 under an applied field Hex = 30 Oe of the YIG/GGG (111) film for the first time. In addition, the sources of the high-frequency magnetic loss in the YIG film were investigated. In detail, the roughness, thickness, and polycrystalline structure, along with the existence of oxygen vacancies and anisotropic fields, influenced the linewidth of the film. This study provides a method to prepare single-crystalline YIG films via room-temperature deposition and ex situ annealing for potential applications in high-frequency microwave devices. Highlights: YIG thin films were prepared by magnetron sputtering and ex situ annealing. The thin film with the lowest magnetic loss was selected by using method of high-throughput material screening. The highest Ms and the lowest line width can be obtained under the optimum preparation parameters of 3 Pa–95 W - 800 °C. Roughness, thickness, polycrystalline structure, oxygen vacancy and anisotropic field will affect the magnetic loss.